Relationship of Interdisciplinary Collaboration on Employee Engagement at a Private Tertiary Hospital in the Philippines - Jesus Briones; Oliver R. Lubiano; Wilmar D. Marqueses; Isabella Vida P. Sicat; Flormando P. Baldovino; Rey Fernan G. Refozar (Inclusive Society and Sustainability Studies, 2025)
Interdisciplinary collaboration is vital in healthcare organizations for enhancing service delivery and employee outcomes. This study, conducted among 190 regular employees of a private tertiary hospital in the Philippines, examined the relationship between key dimensions of interdisciplinary collaboration—communication, mutual respect, role clarity, conflict resolution, and leadership—and employee engagement aspects such as organizational commitment, recognition, growth opportunities, job satisfaction, and affective commitment. Using a descriptive-quantitative design, data were collected through a validated questionnaire distributed via Google Forms and analyzed using frequency distribution, weighted mean, and Spearman’s rank-order correlation. Findings indicated generally strong collaboration, with highest ratings in mutual respect, and role clarity, and moderate performance in communication, leadership support, and conflict resolution. Employee engagement was similarly positive, with strengths in organizational commitment and growth opportunities, while affective commitment, job satisfaction, and recognition were moderate. Significant positive relationships were found between all collaboration and engagement dimensions, highlighting that effective collaboration fosters greater motivation, satisfaction, and organizational attachment. The results align with Social Exchange Theory, suggesting that positive interpersonal interactions cultivate reciprocal commitment and engagement.  Despite the positive ratings, employees reported challenges including the need for stronger interdepartmental support, communication breakdowns, conflicting departmental priorities, and hierarchical role dominance hindering effective collaboration. Building on these insights, the study proposes organizational initiatives to strengthen leadership effectiveness, improve conflict management, and create structured pathways for professional advancement. Embedding these initiatives into daily practice can sustain a motivated workforce, foster cohesive teamwork, and advance patient-centered care.